The effect of transformational leadership on job happiness: The mediating role of work engagement - Marwan Man Soleman; Febriana Wurjaningrum; Rahmat Sabuhari,; Muhammad Asril Arilaha; Sharifah Milda Amirul; Johan Fahri (IRJEMS, 2024)
A happy person will be concerned about what happens to his company and also pay attention to community issues connected to his affairs in the workplace, attempting to understand every change in the company so that he may set an example for other employees. This study examined the direct relationship between transformational leadership and job happiness and work engagement within the State Civil Apparatus (SCA) and the function of work engagement as a mediating variable that connects the two. Three hundred thirty-six government employees from the Ternate City Government served as the samples. The study team gave the questionnaire to the respondents directly. PLS and the structural equation model are the analytical tools utilized to test the hypothesis. The results showed that transformational leadership and work engagement directly affected job happiness. Work engagement can mediate the influence of transformational leadership on SCA job happiness. SCA is expected to have happy, good feelings in the work environment so that the government’s vision and mission can be realized according to the predetermined targets.